Migrants from the countries of the Eurasian Economic Union at the Moscow labour market: socio-professional background - Osadchaya, Galina I. (Journal of the Belarusian State University. Sociology, 2019)
The article shows that the citizens’ labour mobility of the EEU member States corresponds to the needs and the features of the Moscow labour market. It provides replacing workplaces less demanded by the Muscovites not being forced out of the market. The new legal status, which the representatives of the EEU countries received, in a crisis contributed to supporting labour mobility and changing the structure in favour of the workers from the EEU member States. It has been identified that more than 65 % of the migrants’ emotional and appraisal reaction to the change of their status in the Moscow labour market is positive, they could adapt here. Belarusian and Armenian migrants are more successfully harmonized into the Moscow realities. Among not adapted migrants, who take marginal positions in the Moscow megapolis more frequently, are those who come from Kyrgyzstan. The negative attitude of the majority population from the Capital of labour mobility influences migrants’ social well-being. 35 % of the migrants from the EEU member States during their stay in Moscow felt discomfort and experienced discrimination for national and ethnic reason. The farther the cultural distance, the less migrants are desirable. Areas have been substantiated for improvement in the migration and social policy of Moscow based on the analysis of such problems as house hunting, difficulties to get a job, bad conditions for further training and professional growth, negative stereotypes and prejudices from other people, which migrants faced most of all.